Blackless Fantasy: The Disappearance of Race in Massively Multiplayer Online Role-Playing Games - Higgin, Tanner (Games and Culture, 2009)
This article focuses on questioning and theorizing the visual and discursive disappearance of blackness from virtual fantasy worlds. Using EverQuest, EverQuest II, and World of Warcraft as illustrative of a timeline of character creation design trends, this article argues that the disappearance of blackness is a gradual erasure facilitated by multicultural design strategies and regressive racial logics. Contemporary fantasy massively multiplayer online role-playing games (MMORPGs) privilege whiteness and contextualize it as the default selection, rendering any alterations in coloration or racial selection exotic stylistic deviations. Given the Eurocentrism inherent in the fantasy genre and embraced by MMORPGs, in conjunction with commonsense conceptions of Blacks as hyper-masculine and ghettoized in the gamer imaginary, players and designers do not see blackness as appropriate for the discourse of heroic fantasy. As a result, reductive racial stereotypes and representations proliferate while productive and politically disruptive racial differences are ejected or neutralized through fantastical proxies.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé